hubungan kualitas pelayanan dengan kepuasan pasien - Achmad Farich; Dewi Kusumaningsih; Sosya Mona Seprianti (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Integrated Service Post (Posyandu) is one form of community based health efforts which is managed and implemented by volunteer community health workers. That performance is very important to monitor the toddlers. The coverage of toddlers weighed at Ngaras at public health Service has decreased by 2014 reached of 87.0% in 2015 reached of 100.4% in 2016 reached of 64.0% but in 2017 it only reached of 68,2%.Purpose: To know the correlation of knowledge, motivation, training among volunteer community health workers at public health services West Pesisir Province of Lampung  2018.Methods: Quantitative research type with cross sectional design and population recruited  all of volunteer community health workers. Data collected by using questionnaire sheets. Analysis of data used univariate and bivariate (Chi Square).Results: The results showed that the volunteer community health workers have best performance with number of 45 volunteers (69,2%) comparing with who has a poor performance with number of 20 volunteer (30,8%). Based on bivariate analysis following in several parts of the volunteer such as knowledge with  p-value of 0,001 OR 4,889 (1,5 to 15,3 95% CI), motivation with p-value 0,034 OR 3,778 (1,2 to 11,4 95% CI), and the training with p-value 0,009 OR 5,429 (1,6 to 17,8 95% CI).Conclusion: There is a relation of knowledge, motivation and training for the performance of volunteer community health workers. It is suggested to management of public health centre on Ngaras to conduct more intensive training related to volunteer training which includes knowledge sharing which will improve on volunteer community health workers performance on task, and motivation to intensify duty of passion of volunteer community health workers